Sosialisasi Bahaya Pernikahan Dini Sebagai Upaya Pencegahan Stunting Di SMPN 1 Sumberasih - Annisa Rohmania; Nadya Salsa Amelia Pratiwi; Rosyidatuzzahro Anisykurlillah (Cv. Utility Project Solution, 2023)
In this era of rapid progress in social, cultural and economic life, people's habits have changed. One of them is promiscuity which has been considered a common habit. However, there are several community groups that still apply the old culture, there are still many people who marry off their children at an early age. Early marriage occurs due to several factors and also early marriage has a negative impact in the health and psychological fields. The purpose of community service through the socialization of early marriage is to provide education about the dangers of early marriage as an effort to prevent stunting. The methods used in the implementation of this service include surveys, counseling related to the factors and impacts of early marriage. This activity was carried out on May 9, 2023. The results of this service activity for students of SMPN 1 Sumberasih make them know the factors of early marriage, namely, factors of pregnancy outside of marriage, environmental factors, parental / family factors, educational factors, and economic factors. As well as knowing the impact of early marriage, namely, the risk of threatening the lives of mothers and babies, disharmonious families, the economy and the social environment.